PERANCANGAN APLIKASI ABSENSI PEGAWAI MENGGUNAKAN QR CODE PADA BANDARA HALIM PERDANA KUSUMA JAKARTA BERBASIS MOBILE ANDROID - Hadi, Muhammad; Purwanto, Hari (Universitas Dirgantara Marsekal Suryadarma, 2024)
Attendance or attendance card is a document that records the attendance hours of each employee in the company. This employee attendance record can be in the form of a regular attendance list, it can also be in the form of an attendance card filled in with a timekeeping machine. Time recording work can basically be separated into two parts, namely attendance time keeping and shop time keeping. QR codes or commonly known as QR codes are a form of bar code evolution from one dimension to two dimensions. Halim Perdana Kusuma Airport is an airport in Jakarta, Indonesia. The airport is also used as an air command headquarters to become a commercial airport starting January 10, 2014 to divert flights from Soekarno-Hatta International Airport which is considered to be overcrowded. The attendance system at Halim Perdana Kusuma Airport is still manual, namely by signature attendance, so it is possible that there is a difference in attendance calculations. Or cheating on employee attendance. In this case, cheating is in the form of the employee's absence but the attendance is made present. Based on these problems, the authors took the initiative to help the airport by creating an abscessnsi application using qr code and andoid programming language and sqlite as the database.